2018
DOI: 10.1002/rsa.20830
|View full text |Cite
|
Sign up to set email alerts
|

Rapid mixing of hypergraph independent sets

Abstract: We prove that the mixing time of the Glauber dynamics for sampling independent sets on n‐vertex k‐uniform hypergraphs is Ofalse(nnormallognfalse) when the maximum degree Δ satisfies Δ ≤ c2k/2, improving on the previous bound Bordewich and co‐workers of Δ ≤ k − 2. This result brings the algorithmic bound to within a constant factor of the hardness bound of Bezakova and co‐workers which showed that it is NP‐hard to approximately count independent sets on hypergraphs when Δ ≥ 5·2k/2.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…Simultaneous to our work, Hermon, Sly, and Zhang [24] showed that Markov chains for monotone k-CNF formulas are rapidly mixing, if d ≤ c2 k/2 for a constant c. In another parallel work, Moitra [29] gave a novel algorithm to sample solutions for general k-CNF when d 2 k/60 . We note that neither results are directly comparable to ours and the techniques are very different.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Simultaneous to our work, Hermon, Sly, and Zhang [24] showed that Markov chains for monotone k-CNF formulas are rapidly mixing, if d ≤ c2 k/2 for a constant c. In another parallel work, Moitra [29] gave a novel algorithm to sample solutions for general k-CNF when d 2 k/60 . We note that neither results are directly comparable to ours and the techniques are very different.…”
Section: Introductionmentioning
confidence: 66%
“…This indicates that our condition on r in Theorem 25 is necessary for Algorithm 6. In contrast, Hermon et al [24] show that on a linear hypergraph (including the hypertree), the Markov chain mixes rapidly for degrees higher than the general bound. It is unclear how to combine the advantages from these two approaches.…”
Section: Running Time Analysis Of Algorithmmentioning
confidence: 91%
“…Simultaneous to our work, Hermon et al [24] showed that Markov chains for monotone k-CNF formulas are rapidly mixing, if d ≤ c2 k /2 for a constant c. In another parallel work, Moitra [29] gave a novel algorithm to sample solutions for general k-CNF when d 2 k /60 . We note that neither results are directly comparable to ours, and the techniques are very different.…”
Section: Introductionmentioning
confidence: 57%
“…Unfortunately, our algorithm can be exponentially slow when the intersection s is not large enough. In sharp contrast, as shown by Hermon et al [24], Markov chains mix rapidly for d ≤ c2 k /k 2 when s = 1.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation